The impact of a standardised ketamine step protocol for cancer neuropathic pain. (2nd January 2022) - Provido-Aljibe, Mahrley T.; Yee, Choon Meng; Low, Zhi Jun Carin; Hum, Allyn
Abstract : Context: Ketamine at sub-anesthetic doses is a potent analgesia. Its use in cancer pain remains equivocal with protocols varying in patient selection, starting dose, titration, duration of use and adjustment of co-analgesics. Objective: To study the impact of a standardised Ketamine Step Protocol on cancer pain in a Palliative Care Unit (PCU). Methodology: This is a prospective cohort study of a standardised Ketamine Step Protocol which was developed in a PCU for use in cancer pain. The subcutaneous ketamine infusion was standardised at a starting dose of 75 mg over 24 hours with Haloperidol 5 mg as prophylaxis against psycho-mimetic side effects. Incremental doses of ketamine followed the daily stepwise protocol. Result: Of the 48 patients analysed, 41 (85.4%) had neuropathic cancer pain. The median Palliative Performance Scale score (PPSv2) was 40%. Mean Numerical Rating Score (NRS) improved from 6.74 to 2.61 ( P < 0.0001) with a mean percentage reduction of 58.05%. The final mean daily ketamine dose needed to achieve stable pain control was 137.50 mg/day (±81.54). 31(62.5%) patients achieved pain control by day 3. The mean Morphine Equivalent Daily Dose (MEDD) reduction was from 130.34 mg to 107.33 mg ( P < 0.002) with a percentage reduction of 18.85%. More than half of our patients completed the 5 d protocol with mild to moderate side effects not warranting urgent medical intervention nor termination of the ketamine protocol. Conclusion: Use of a standardised Ketamine Step Protocol showed a statistically significant reduction in pain and MEDD in patients with predominantly neuropathic cancer pain. It also demonstrated a safe and effective method for opioid reduction after commencement of parenteral ketamine. Key Message: How can a standardised ketamine protocol impact on cancer pain control?: Our study shows that: Parenteral ketamine is a potent analgesic which significantly reduced pain in patients with cancer neuropathic pain. This study also demonstrated a safe and effective method for titration of opioids after parenteral ketamine is started. Concurrent use of psychotropics also helps to reduce psycho-mimetic side effects, increasing tolerability to ketamine.